Climatic and atmospheric determinants of sensor-type biases in measured solar irradiance - Yazan J.K. Musleh (23715429) (2026)
Accurate plane-of-array (POA) irradiance measurements are critical for assessing photovoltaic (PV) performance, yet systematic discrepancies between thermopile pyranometers and silicon-based instruments remain underexplored across varying climates. This work quantifies the measurement biases of silicon-based sensors relative to thermopile, using data from eight globally distributed sites covering arid, tropical, subtropical, and temperate regimes. While overall correlations were strong, consistent offsets of -12.5 to +3.5 W/m2 emerged, largely influenced by solar geometry, sky clarity, and aerosol conditions. Reference cells tended to under-respond under clear, beam-dominated skies, but showed slight over-responses in diffuse-rich or cloud-enhanced environments. Three empirical correction schemes were developed and tested using six sites for training (70/30 split). A geometry-only model based on solar zenith angle (SZA) provided limited improvement, whereas incorporating both SZA and the clearness index (Kt) yielded consistent error reductions across climates. At the arid Qatar site, for instance, the Root Mean Square Deviation (RMSD) dropped from 4.2% to 2.8%, with bias effectively eliminated. Independent testing at two temperate settings confirmed the approach’s robustness, with the SZA and Kt formulation offering the most balanced and transferable correction. Overall, combining solar geometry with sky-clarity metrics provides a simple yet effective cross-climate framework, reducing RMSD by roughly 0.5-1% and Mean Bias Deviation (MBD) by 1-2%. The method enables reliable harmonization between pyranometer and reference-cell measurements, improving the accuracy of POA inputs for PV modelling and long-term system evaluation. Other Information Published in: Solar Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.solener.2026.114592